2006
DOI: 10.1021/es051921i
|View full text |Cite
|
Sign up to set email alerts
|

Electrodialysis for Recovering Salts from a Urine Solution Containing Micropollutants

Abstract: Electrodialysis was investigated for the separation of micropollutants from nutrients in anthropogenic urine. In a continuously operated process, the nutrients were concentrated up to a factor of 3.2. The concentration factor was limited by water transport across the membrane. Water transport was caused by osmosis and electroosmosis, and a model was developed to describe these phenomena. The removal of several spiked micropollutants was investigated in continuous electrodialysis experiments. Ethinylestradiol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 26 publications
7
93
0
Order By: Relevance
“…After the feed solution was separated, sorption continued within the diluate and concentrate at pH 7; indicating sorption to both the AEMs and CEMs. This confirms the results by Pronk et al [33] whereby neutral compounds were assumed to sorb to both AEMs and CEMs. Above pH 10, ES degradation results from cleavage of the cyclic sulfite group [10] leading to the formation of ES diol.…”
Section: Endosulfan Sorption In Electrodialysissupporting
confidence: 92%
See 1 more Smart Citation
“…After the feed solution was separated, sorption continued within the diluate and concentrate at pH 7; indicating sorption to both the AEMs and CEMs. This confirms the results by Pronk et al [33] whereby neutral compounds were assumed to sorb to both AEMs and CEMs. Above pH 10, ES degradation results from cleavage of the cyclic sulfite group [10] leading to the formation of ES diol.…”
Section: Endosulfan Sorption In Electrodialysissupporting
confidence: 92%
“…Pronk et al [33] studied the sorption of the hormone 17α-ethinylestradiol (75% initial mass sorbed) to ion-exchange membranes during batch ED experiments for the treatment of urine and postulated that sorption was due to hydrophobicity. However, a study by Banasiak [34] suggested that trace organic sorption (of steroidal hormones) to ion-exchange membranes was influenced by mechanisms other than hydrophobic interactions.…”
Section: Endosulfan Sorption Mechanismsmentioning
confidence: 99%
“…However, coupling biological nutrient stabilization with the postnitrification steps of distillation and advanced treatment can improve the quality of the liquid fertilizer by inactivating pathogens and removing pharmaceuticals, respectively. Several treatment processes have been successfully tested for the removal of pharmaceuticals from stored urine: ozonation (Dodd et al, 2008), electrodialysis (Pronk et al, 2006a), and nanofiltration (Pronk et al, 2006b). Treatment with activated carbon was shown to be an effective process for pharmaceutical removal from nitrified urine ( € Ozel Duygan et al, 2015).…”
Section: Urine Nitrification For Nutrient Stabilizationmentioning
confidence: 99%
“…The only studies are on the applicability of ED for salts recovery from a urine solution containing xenobiotics [37,105]. Although high removal of 17α-ethinylestradiol is obtained [37], Pronk et al [105] showed that xenobiotics such as CBZ and propanolol readily adsorb on the membranes, where electrostatic, size exclusion and hydrophobic interactions play a role in the adsorption behaviour. More hydrophobic compounds seem to adsorb more.…”
Section: Electrodialysismentioning
confidence: 99%